Development of a simple and rapid method for the specific identification of organism causing anthrax by slide latex agglutination. (16th December 2013) - Sumithra, T.G.; Chaturvedi, V.K.; Gupta, P.K.; Sunita, S.C.; Rai, A.K.; Kutty, M.V.H.; Laxmi, U.; Murugan, M.S.
Abstract A specific latex agglutination test (LAT) based on anti‐PA (protective antigen) antibodies having detection limit of 5 × 104 formalin treated Bacillus anthracis cells or 110 ng of PA was optimized in this study. The optimized LAT could detect anthrax toxin in whole blood as well as in serum from the animal models of anthrax infection. The protocol is a simple and promising method for the specific detection of bacteria causing anthrax under routine laboratory, as well as in field, conditions without any special equipments or expertise. Significance and Impact of the Study The article presents the first report of a latex agglutination test for the specific identification of the cultures of bacteria causing anthrax. As the test is targeting one of anthrax toxic protein (PA), this can also be used to determine virulence of suspected organisms. At the same time, the same LAT can be used directly on whole blood or sera samples under field conditions for the specific diagnosis of anthrax.